2010
DOI: 10.2215/cjn.02680310
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Control of 1,25-Dihydroxyvitamin D and FGF23 Formation Involving the FGF23/Klotho System

Abstract: agonists is important for the control of phosphate and calcium homeostasis and bone remodeling but could also have beneficial effects by reducing the risk for development of cardiovascular morbidity and mortality, diabetes, autoimmune diseases, and cancer. Microarray assay studies suggested that more than 150 human genes are directly regulated by calcitriol through vitamin D-responsive elements (VDREs) in their promoters (1). Circulating calcitriol is mainly synthesized by the renal proximal tubule. Calcitriol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 61 publications
1
86
0
4
Order By: Relevance
“…PTH is responsible for increasing 1α-hydroxylase transcription; therefore, the effect of 1,25-(OH) 2 D on PTH provides an indirect mechanism by which 1,25-(OH) 2 D down-regulates its production [49]. Rising concentrations of 1,25-(OH) 2 D also increase the expression of the phosphaturic factor, fibroblast growth factor 23 (FGF23) [51]. FGF23 suppresses the expression of 1α-hydroxylase in the kidney, providing another indirect pathway of 1,25-(OH) 2 D acting to downregulate its production [52].…”
Section: Maintenance Of Homeostasismentioning
confidence: 99%
“…PTH is responsible for increasing 1α-hydroxylase transcription; therefore, the effect of 1,25-(OH) 2 D on PTH provides an indirect mechanism by which 1,25-(OH) 2 D down-regulates its production [49]. Rising concentrations of 1,25-(OH) 2 D also increase the expression of the phosphaturic factor, fibroblast growth factor 23 (FGF23) [51]. FGF23 suppresses the expression of 1α-hydroxylase in the kidney, providing another indirect pathway of 1,25-(OH) 2 D acting to downregulate its production [52].…”
Section: Maintenance Of Homeostasismentioning
confidence: 99%
“…In this way soluble KLOTHO regulates various ion channels and transporters (184), and growth factor signaling [including Wnt, IGF-I, and transforming growth factor (TGF)-␤1] (257,426 (444) (Fig. 4) (142,318) (Fig. 4).…”
Section: (See the Role Of Sirtuins In Cr)mentioning
confidence: 99%
“…Already more than 35 years ago (Guéguen,1982), reliable studies had estimated the obligatory losses of P in feces (Wilkinson, 1976) and urine (Robertson, 1976) Without this knowledge, it is impossible to give an upper limit of daily or chronic phosphorus intake. Anyway, it has been shown that FGF-23 increases not only with phosphorus intake but also when GFR (glomerular filtration rate) falls below 70 ml/min (19). Knowing this, it is obvious, that any compromised renal function (i.e.…”
Section: Appendix B -Full List Of Comments Submitted By Means Of the mentioning
confidence: 99%